2003
DOI: 10.2308/accr.2003.78.1.193
|View full text |Cite
|
Sign up to set email alerts
|

Analyst Forecast Revisions and Market Price Discovery

Abstract: We document several factors that help explain cross-sectional variations in the post-revision price drift associated with analyst forecast revisions. First, the market does not make a sufficient distinction between revisions that provide new information (“high-innovation” revisions) and revisions that merely move toward the consensus (“low-innovation” revisions). Second, the price adjustment process is faster and more complete for “celebrity” analysts (Institutional Investor All-Stars) than for more obscure ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
402
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 671 publications
(457 citation statements)
references
References 35 publications
43
402
1
2
Order By: Relevance
“…Elgers et al (2001) offer support for the argument that the market's earnings expectations may fail to incorporate some portion of the value-relevant information in analysts' earnings forecasts. Gleason and Lee (2003) also find abnormal returns present after analysts forecast revisions. Zhang (2006) reports that investors underreact to new information and that good news will be associated with higher future returns.…”
Section: Introductionmentioning
confidence: 95%
“…Elgers et al (2001) offer support for the argument that the market's earnings expectations may fail to incorporate some portion of the value-relevant information in analysts' earnings forecasts. Gleason and Lee (2003) also find abnormal returns present after analysts forecast revisions. Zhang (2006) reports that investors underreact to new information and that good news will be associated with higher future returns.…”
Section: Introductionmentioning
confidence: 95%
“…I then compute earnings per share based on the third quarter estimate of the effective tax rate I also include book-to-market ratio (BM), the natural log of total assets (Size), and cumulative size-adjusted returns for the six months preceding the earnings announcement (Momentum). These three controls are commonly used in finance and accounting capital market studies (e.g., Fama andFrench 1992, Gleason andLee 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Gleason and Lee (2003) found that high-innovation forecast revisions (new forecast above the analyst's prior forecast and the consensus forecast, or below both forecasts) have a greater price effect than low-innovation forecasts. As a result, This is the Pre-Published Version we expect analysts to be more concerned about readability in case of high innovation forecast than low innovation forecasts.…”
Section: This Is the Pre-published Versionmentioning
confidence: 99%
“…We expect that if readability is a credible signal of accuracy, then readability has greater influence on investment decisions when analyst reports contain upward revisions rather than downward revisions. We further hypothesize that forecast accuracy is more related to readability when the forecasts result in upward revision of future 1 Prior studies suggest that markets have stronger response towards analyst forecast revisions when the forecast is expected to be more accurate (Abarbanell et al, 1995;Stickel, 1992;Park and Stice, 2000;Gleason and Lee, 2003;and Clement and Tse, 2003). This is the Pre-Published Version earnings expectations.…”
Section: Introductionmentioning
confidence: 99%